2022
DOI: 10.1002/ctm2.1091
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MRAP protein family as broad‐spectrum GPCR modulators

Abstract: Background The melanocortin receptor accessory proteins (MRAP1 and MRAP2) are well‐known endocrine regulators for the trafficking and signalling of all five melanocortin receptors (MC1R–MC5R). The observation of MRAP2 on regulating several non‐melanocortin G protein‐coupled receptors (GPCRs) has been sporadically reported, whereas other endogenous GPCR partners of the MRAP protein family are largely unknown. Methods Here, we performed single‐cell transcriptome analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…We performed a protein alignment analysis and found that the S19 and Y250 in MC2R were not conserved in the newly identified GPCRs that bind to MRAP1 from our study ( Fig. 2 ) ( Wang et al, 2022 a). This is probably because MRAP1 needs this interface to regulate MC2R activity but not for direct interaction.…”
Section: The Structural Insight Of Ligand Recognition and Gpcr Activa...mentioning
confidence: 86%
See 1 more Smart Citation
“…We performed a protein alignment analysis and found that the S19 and Y250 in MC2R were not conserved in the newly identified GPCRs that bind to MRAP1 from our study ( Fig. 2 ) ( Wang et al, 2022 a). This is probably because MRAP1 needs this interface to regulate MC2R activity but not for direct interaction.…”
Section: The Structural Insight Of Ligand Recognition and Gpcr Activa...mentioning
confidence: 86%
“…Benefiting from the rapid development of multi-omics technologies, we first acquired numerous metabolic-related GPCRs that coexpressed with MRAP2 in the same neurons via single-cell RNA sequencing (scRNA-seq). Next, we experimentally screened the majority of GPCRs and found that they not only exhibited direct interactions with MRAP2 proteins but also pharmacologically regulated by MRAP2 in terms of cell surface expression and ligand-induced downstream cascades ( Wang et al, 2022 a). This work redefined MRAP proteins as broad-spectrum modulators of metabolic-related GPCR signaling in vitro and in vivo ( Fig.…”
Section: The New Exploration Of the Mrap Familymentioning
confidence: 99%
“…This type of regulator binds an allosteric site that is distinct from the orthosteric site recognised by endogenous ligands and stabilises a specific receptor conformation. The characterisation of the natural allosteric modulation of GPCRs is a promising new approach for GPCR drug discovery compared to classical approaches that focus on the development of small molecules targeting the orthosteric site [51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…MRAP exhibits protein‐protein interactions and distinct pharmacological properties on surface translocation, homeodomain activity, and ligand‐stimulated downstream signaling of these GPCRs. [ 122 ] Prokinetic peptides (PKs) are agonists of G protein‐coupled receptors: prokinetic receptors (PKRs), and they reduce food intake in rodents. The inhibition of food intake by PKs is mediated through amygdala PKR2 neurons.…”
Section: The Mc4r Signaling Pathwaymentioning
confidence: 99%